Autonomy-supportive physical education, harmonious passion, and mental health in adolescent girls during COVID-19 - Solmaz Babaei; Masoumeh Parvaneh (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: A crucial issue for the health of children and adolescents is understanding how to boost their level of physical activity during the COVID-19 outbreak. The pandemic has limited opportunities for engaging in physical activity, even for activities that students find enjoyable. Materials & Methods: This study investigates students’ autonomy in sports to foster harmonious passion for physical activity and mental health. Self-determination theory was used as the theoretical framework. A total of 236 female students (Mage = 15.36) participated in a 16-week research project. Samples were randomly divided into an autonomy-support group and a control group. Results: The results showed that the experimental group had more harmonious passion (p < 0.05). They also reported more physical activity, less loneliness, and greater mental vitality (p < 0.05). Conclusion: Physical education based on autonomy support during the COVID-19 pandemic was effective in fostering harmonious passion for physical activity and reducing the negative psychological consequences of virus outbreaks.